Clinical assessment and management of liver fibrosis in non-alcoholic fatty liver disease - Campos-Murguía, Alejandro; Ruiz-Margáin, Astrid; González-Regueiro, José A; Macías-Rodríguez, Ricardo U (World journal of gastroenterology : WJG, 2020)
Non-alcoholic fatty liver disease (NAFLD) is among the most frequent etiologies of cirrhosis worldwide, and it is associated with features of metabolic syndrome; the key factor influencing its prognosis is the progression of liver fibrosis. This review aimed to propose a practical and stepwise approach to the evaluation and management of liver fibrosis in patients with NAFLD, analyzing the currently available literature. In the assessment of NAFLD patients, it is important to identify clinical, genetic, and environmental determinants of fibrosis development and its progression. To properly detect fibrosis, it is important to take into account the available methods and their supporting scientific evidence to guide the approach and the sequential selection of the best available biochemical scores, followed by a complementary imaging study (transient elastography, magnetic resonance elastography or acoustic radiation force impulse) and finally a liver biopsy, when needed. To help with the selection of the most appropriate method a Fagan's nomogram analysis is provided in this review, describing the diagnostic yield of each method and their post-test probability of detecting liver fibrosis. Finally, treatment should always include diet and exercise, as well as controlling the components of the metabolic syndrome, +/- vitamin E, considering the presence of sleep apnea, and when available, allocate those patients with advanced fibrosis or high risk of progression into clinical trials. The final end of this approach should be to establish an opportune diagnosis and treatment of liver fibrosis in patients with NAFLD, aiming to decrease/stop its progression and improve their prognosis.